Kepribadian Guru Pendidikan Agama Islam Menurut Buya Hamka - Hamidah, Laila; Siregar, Sawaluddin; Nuraini, Nuraini (Tarbiyah : Jurnal Ilmiah Kependidikan, 2019)
The teacher is a position or profession that requires special skills as a teacher. This work cannot be done by people who do not have the expertise to carry out activities or work as a teacher. Every teacher has a different personality and background and teaching experience. Every teacher has a personality according to the characteristics they have. Personality is actually an abstract, can only be seen through appearance, action, speech, how to dress, and how to deal with every problem. The teacher's personality is the main capital in carrying out the role and duty as an educator. Personality, character is a crown for a human, because that is what distinguishes humans from animals. Good character does not just appear, it is a lifelong learning process. To grow good character, a teacher can learn about the lives of characters who are considered to have good character or personality. Buya Hamka is a National figure who can be a role model in learning to have a great character and personality. The research conducted was included in the type of qualitative descriptive research with library research. The method used is critical analytical descriptive, the primary data source is the works of Buya Hamka who deal with professional teachers and the secondary data are similar works that have the same theme. The analysis in this study uses the method of content analysis. The results of the study are that the teacher according to Hamka functions as an institution that seeks to develop all the potential that exists in students to the fullest, in accordance with the rhythms of their development, both physicaly and mental spiritual have a good personality because students will imitate the behavior of his teacher. Teacher's Personality in Islamic Education According to Buya Hamka's Thought, the teacher must understand the concept of the educator as an exemplary subject, the tasks of the educator, and have character (traits), as befits an educator. Hamka expressed his opinion about how should the characteristics of Islamic religious education teachers, namely: 1) Having extensive knowledge, 2) Good communication, 3) Good example for students and those around them, 4) Ikhlash, 5) Having  good methods for teaching, 6) Humility, 7) Responsibility, 8) Confidence, 9) Gentleness, 10) Patience, 11) Passion, 12) Apply and say honestly. Relevance of Hamka's Thought about the Teacher's Personality of Islamic Education with Education Today Teachers should help shape the character, mind, character, and personality of students, so that he knows which is good and what is bad. While Islamic teaching is an attempt to fill the intellectuals of students with a number of knowledge. Keyword: Teacher Personality, Buya Hamka